The Effect of Card Box Game Strategy on the Speaking Ability of Young Children - Derminasari, Derminasari; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study investigated the effect of a card box game strategy on the speaking ability of young children in Group A (aged 4–5 years) at One-Roof Kindergarten SDN 146 Kayu Laut, Mandailing Natal Regency, Indonesia, in the 2025–2026 academic year. The intervention addressed low speaking skills characterized by limited vocabulary, reluctance to express opinions, and minimal oral interaction among peers. A quantitative approach with a quasi-experimental one-group pretest–posttest design was employed. Fifteen children participated in four sessions of learning activities using a card box game, an educational medium containing thematic pictures and symbols designed to stimulate oral language. Speaking ability was assessed through observation on three indicators: mentioning familiar words, answering questions appropriately, and imitating writing and pronouncing letters. The mean pretest score was 48.00, with most children categorized as “Not Yet Developed” or “Starting to Develop”. After the intervention, the mean posttest score increased to 82.67, with a predominance of the “Very Well Developed” category. A paired-samples t-test yielded t(14) = 15.53, exceeding the critical value at the 5% significance level, indicating a statistically significant improvement. These findings demonstrate that the card box game strategy is an effective, play-based approach for enhancing young children’s speaking ability